Two Poems - Onart, Adnan Adam (Radical Teacher, 2023)
These poems are trying to tell the life stories of two generations of immigrants. Grand-parents immigrated from Crimea to Ottoman Empire, a superpower at the time, but imploding shortly after to a small modern republic, still in trouble, and the grand-children immigrated to the States, a superpower, and experiencing the fear that she might also become soon a third-world country. I prefer not to explicate my poems, they should speak independently. This time, I felt the urge to tell the background story. Forgive my intrusion.